Association of plasma CD40L with acute chest syndrome in sickle cell anemia. (September 2017) - Garrido, Vanessa Tonin; Sonzogni, Laura; Mtatiro, Siana Nkya; Costa, Fernando F.; Conran, Nicola; Thein, Swee Lay
Highlights: High plasma CD40L is associated with a history of ACS in SCA. CD40L correlates with hemolysis markers only in SCA patients with no history of ACS. Platelet activation may play a role in the pathophysiology of ACS. Plasma CD40L may represent a potential marker of susceptibility to ACS in SCA. Abstract: Platelet activation and platelet-derived cytokines contribute to the vascular inflammation and increased thrombotic activity known to occur in patients with sickle cell anemia (SCA). CD40 ligand (CD40L), a platelet-associated pro-inflammatory molecule that promotes endothelial cell activation, is elevated in the circulation of SCA patients. We sought to evaluate the association of CD40L and inflammation with sickle-related clinical complications and laboratory variables in SCA patients. Soluble CD40L, thrombospondin (TSP)-1 and tumor necrosis factor (TNF)-α were determined in the platelet-poor plasma of healthy individuals and steady-state SCA patients by ELISA. Lifetime clinical complications were verified by detailed review of patients' medical records. We found that plasma CD40L was associated with acute chest syndrome (ACS), and that SCA patients with a lifetime history of ACS (ACS+) presented significantly higher plasma CD40L and TSP-1 than patients who had never experienced ACS (ACS−). In the ACS+ group, both platelet-derived proteins (CD40L and TSP-1) correlated with mean corpuscular volume, mean corpuscular hemoglobin and reticulocyte hemoglobin, while in the ACS− group, CD40L correlated with low red blood cell counts, hemoglobin, hematocrit and lactate dehydrogenase, and TSP-1 correlated with reticulocyte percentage and white blood cell count. As expected, CD40L and TSP-1 correlated with platelet counts in both groups. These data highlight the possible role of platelet activation in ACS and suggest that plasma sCD40L, together with TSP-1, may represent a potential marker of susceptibility to ACS in SCA.